Long-Term Anti-Corrosion Performance of Ultra-High Content Inhibitor Loaded Gel-Epoxy Solid Inhibitor with Temperature-Responisve Effect - Ying Zhao; Qing Yang; Ali Hussein Khalaf; Bing Lin; Junlei Tang (Applied Sciences)
This study investigates the development and performance of a novel GE-EP@OIM solid corrosion inhibitor for enhancing long-term corrosion protection in the oil-and-gas industry’s corrosive environment. The inhibitor was synthesized by incorporating organic imidazole molecules (OIMs) into a Gel-Epoxy (GE-EP) matrix, achieving an OIM-loading capacity of approximately 34.75% (generally reported capacity is up to 20%). The solid inhibitor was designed as a smart material, which exhibits temperature-responsive release behavior in a chlorine-corrosive environment. A combination of electrochemical measurements, weight loss testing, and scanning electron microscopy (SEM) was employed to assess the inhibitor’s performance. The results demonstrate that GE-EP@OIMs significantly improve corrosion resistance, particularly at elevated temperatures (50 °C), with the long-term protection effect serving as a key highlight, maintaining efficacy for up to 60 days, and it shows enhanced stability compared to conventional inhibitors. While the mechanical properties of GE-EP@OIMs are slightly diminished due to the incorporation of OIMs, the inhibitor still meets the necessary fluidity and performance criteria for medium- to long-term applications. This material shows considerable promise for mitigating corrosion in oilfield operations, especially for downhole tubing, and presents a cost-effective solution to the widespread corrosion challenges in the industry.